IDDF2018-ABS-0146 The knowledge and perceptions on colorectal cancer (CRC) screening in general population: a 10-year comparison. (June 2018) - Huang, Junjie; Choi, Peter; Lok, Veeleah; Chen, Chunlan; Leung, Colette; Wang, Ada; Huang, Jason; Wong, Martin
Abstract : Background: The incidence of colorectal cancer (CRC) is increasing yet the rate of screening uptake remains suboptimal. We aimed to evaluate how the knowledge and perceptions towards CRC screening have been changing in a general population which has implemented a government subsidised screening programme. The objective of the present study is to compare the knowledge level and perceived barriers to CRC screening between 2006 and 2016–2017 in a general public based on the Health Belief Model (HBM). Methods: Two cross-sectional, population-based studies were conducted by simple random sampling based on telephone interviews in 2006 and 2016–2017 respectively, including 1004 and 2, 400 Chinese adults. The survey instrument used to measure the variables pertinent to the HBM, including the knowledge of the CRC, perceived susceptibility, severity, benefit, barriers, and cues to action for the CRC, has been validated by an expert panel. The changes of these factors were tested using the Pearson's chi-square test. Results: The results were shown in table 1. The proportion having a high level of knowledge (score ≥2) of CRC risk factors (34.0% vs. 16.0%), and CRC screening tests (67.4% vs. 42.4%) in 2016–2017 was higher than those in 2006 (both p<0.001). The proportion of subjects having high perceived severity score (≥14) was greater in 2016–2017 (37.9%) than in 2006 (29.2%). In contrast, the perceived health/psychological and access barriers have decreased. A significantly higher proportion of subjects reported physician recommendations for CRC screening in 2016–2017 (55.3% vs. 8.4%). Other variables pertinent to HBM were not significant factors in the analysis. Conclusions: Based on the HBM, the knowledge of CRC risk factors; CRC screening tests; perceived severity of CRC increased, while perceived barriers to CRC testing decreased since 2006. Higher proportion received physician recommendations for CRC screening. These findings may imply the effectiveness of the government screening programme or impact of more intensive educational initiatives in the general population. This cause-and-effect relationship should be examined in future studies.